Cyclic RGD functionalized PLGA nanoparticles loaded with noncovalent complex of indocyanine green with urokinase for synergistic thrombolysis - Zhang, Sha; Li, Jinjie; Ren, Jiefeng; Xue, Zaiyao; Qi, Xinlian; Si, Quanjin (Frontiers in Bioengineering and Biotechnology, 2022)
Thrombotic diseases have the characteristics of long latency period, rapid onset, and high mortality rate, which seriously threaten people's life and health. The aim of this research is to fabricate a novel indocyanine green complex of urokinase (ICG@uPA) and employ the amphiphilic PEG-PLGA polymer to deliver the complex as an enzyme-phototherapeutic synergistic thrombolysis platform. The noncovalent indocyanine green (ICG) complex of urokinase (ICG@uPA) was prepared via supramolecular self-assembly and then encapsulated into cRGD decorated polymeric nanoparticles (cRGD-ICG-uPA NPs) by double-emulsion solvent evaporation method. Then the nanoparticles (NPs) were characterized in terms of particle size, optical properties, in vitro release, etc. The targeting and thrombolytic effect of the nanoparticles were studied both in vitro and in vivo. ICG@uPA and cRGD-ICG-uPA NPs displayed significantly higher photostability and laser energy conversion efficiency than free ICG. Concomitantly, the NPs exhibited selective binding affinity to the activated platelets and specific accumulation in the mouse mesenteric vessel thrombus. Significant thrombolysis was achieved in vivo by photo-assisted synergistic therapy with reduced dose and systemic bleeding risk of uPA. Our results prove that the functional PLGA nanoparticle loaded with the ICG@uPA offers a novel option for effective and safe thrombolytic treatment.